The Effectiveness of Human Resource Management Strategies in Increasing Employee Loyalty at PT Valbury Asia Futures Medan Branch - Nadia Sari Situmorang; Sri Ramadhani; Tri Inda Fadhila Rahma (SENTRALISASI, 2026)
This study aims to analyze the effectiveness of human resource management (HRM) strategies in improving employee loyalty at PT Valbury Asia Futures Medan Branch. A qualitative descriptive approach was employed. Data were collected through in-depth interviews, observations, and documentation involving Financial Consultants (FC), Senior Financial Consultants (SFC), and management. Informants were selected using purposive sampling based on at least three months of work experience and understanding the companys work system. The findings show that the companys HRM strategies are primarily result-oriented, emphasizing performance-based compensation, high work targets, and reward and punishment mechanisms. Although the compensation system increases employee motivation, it has not effectively improved employee loyalty because of high work pressure and penalty policies. Furthermore, the absence of structured training programs, suboptimal implementation of standard operating procedures (SOP), and a highly competitive work environment also affect employee loyalty. Employee loyalty is reflected through responsibility, commitment, and willingness to remain with the company, although it tends to fluctuate. Overall, the effectiveness of HRM strategies at PT Valbury Asia Futures Medan Branch is not yet optimal because performance targets are not balanced with employee development. Therefore, improvements are needed through adjusting work targets, strengthening training programs, optimizing SOP implementation, and creating sustainable.